Thuggery Practices: Their Impact on Investment Development in Indonesia - Rieneke Ryke Kalalo; Sri Sungkowati; Muhamad Azkia; Ade Risna Sari; Asterina Anggraini (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study is a qualitative study with a descriptive approach, namely an approach that details the main topics in this article. These main topics include thuggery, investment, and investment decisions. The data used in this study is secondary data obtained by the researcher from various credible sources such as scientific articles, books, scientific magazines, and other sources commonly used in any research. The data used is analyzed through the stages of data collection, data reduction, data selection, and concluding. The result in this article show that the phenomenon of thuggery can damage investment development. The Chairman of the Industrial Estate Association (HKI), Sanny Iskandar, revealed that thuggery hampers investment. He stated that losses amount to hundreds of trillions due to cancelled investments and withdrawals from industrial areas. Investors flee because many community organizations or mass organizations force their involvement in the construction process or factory activities. In addition to Sanny Iskandar's opinion above, the Kompas investigative team's report results found that thuggery in industrial areas is a serious obstacle to investment. This disruption occurs systematically and involves community organizations, officials, and village officials who often use their positions to pressure companies